The role of interleukin-1 in perinatal inflammation and its impact on transitional circulation - Owen, Josephine C.; Garrick, Steven P.; Peterson, Briana M.; Berger, Philip J.; Nold, Marcel F.; Sehgal, Arvind; Nold-Petry, Claudia A. (Frontiers in Pediatrics, 2023)
Preterm birth is defined as delivery at <37 weeks of gestational age (GA) and exposes 15 million infants worldwide to serious early life diseases. Lowering the age of viability to 22 weeks GA entailed provision of intensive care to a greater number of extremely premature infants. Moreover, improved survival, especially at extremes of prematurity, comes with a rising incidence of early life diseases with short- and long-term sequelae. The transition from fetal to neonatal circulation is a substantial and complex physiologic adaptation, which normally happens rapidly and in an orderly sequence. Maternal chorioamnionitis or fetal growth restriction (FGR) are two common causes of preterm birth that are associated with impaired circulatory transition. Among many cytokines contributing to the pathogenesis of chorioamnionitis-related perinatal inflammatory diseases, the potent pro-inflammatory interleukin (IL)-1 has been shown to play a central role. The effects of utero-placental insufficiency-related FGR and in-utero hypoxia may also be mediated, in part, via the inflammatory cascade. In preclinical studies, blocking such inflammation, early and effectively, holds great promise for improving the transition of circulation. In this mini-review, we outline the mechanistic pathways leading to abnormalities in transitional circulation in chorioamnionitis and FGR. In addition, we explore the therapeutic potential of targeting IL-1 and its influence on perinatal transition in the context of chorioamnionitis and FGR.